Characterisation of pulsing flow in trickle-bed reactors using ultra-fast magnetic resonance imaging - Nguyen, Thoa T. M.; Sederman, Andrew J.; Gladden, Lynn F. (Diffusion Fundamentals, 2009)
We use ultra-fast Magnetic Resonance Imaging (MRI) to characterise hydrodynamics during pulsing flow in trickle-bed reactors. One-dimensional (1-D) liquid holdup profiles along the flow direction were acquired using Fast Low Angle SHot (FLASH) MRI at spatial and temporal resolutions of 352 μm pixel-1 and 3.3 ms, respectively. Liquid pulse properties such as pulse velocity, duration and frequency obtained with MRI are in good agreement with those measured using a well established technique called the conductance method. In addition, MRI gives local measurements and provides additional spatial information to track individual liquid pulses, which cannot be obtained with the conductance method approach.